Up-Regulation of miR-195 Expression Leads to Decreased Expression of Basic Fibroblast Growth Factor in CLL Patients Treated with DNA Methylation Inhibitors - Phillips, John D.; Pop, Ioana; Boucher, Ken; Yu, Margaret K. (Blood, 2007)
A higher than age-expected DNA methylation index is predictive for early disease progression in patients with CLL (Yu et al. Leukemia Research 2006). We hypothesized that miRNA expression can also be silenced by promoter hypermethylation in CLL. Thus, methyl pool or DNA methyltransferase inhibitors can upregulate microRNAs with tumor suppressor characteristics by restoring the “normal” pattern of methylation. Results of patients treated with cladribine, a methyl substrate inhibitor, or 5-azacitidine, a DNA methyltransferase inhibitor were compared in 2 separate clinical protocols. The global DNA methylation decreased after treatment with cladribine or 5-azacitidine in 60% of the patients. At the 2006 ASH meeting, we reported on the consistent upregulation of miR-17-3p, miR-21, miR-29a, miR-29b, miR-29c, miR-30e, miR-104, miR-126, miR-128a, miR-130a, miR-141, miR-142-3p, miR-148a, miR-151, miR-199a, miR-199a*, and miR-301 by real-time PCR using the Early Access Human Panel from Applied Biosystems. Data from two patients on the cladribine protocol and 10 patients on the 5-azacitidine protocol were used for statistical analyses. Non-parametric Wilcoxon tests as well as t-tests were performed. Comparisons were made of the responders versus non-responders, and of cladribine versus 5-azacytidine. Since many of the miRNAs showed differences in the cladribine versus 5-azacytidine comparison, a second responder vs non-responder analysis was performed in which the two cladribine subjects were removed. MiR-195 was statistically more upregulated in the cladribine treated responder whereas miR-29c was statistically most upregulated in the 5-azacitidine treated patients (p=0.02). In the patients with global demethylation after treatment, upregulation of microRNA-195 was observed and directly correlated with regional demethylation of the CpG island, confirmed by bisulfite sequencing. Some of the predicted targets of miR-195 include bcl-2, CNOT6L, USP15, PADAH1B1, and ESRRG. MiR-195 may also have tumor suppressor characteristics as it also targets basic fibroblast growth factor (FGF-2), a gene important in CLL angiogenesis. There has been some evidence suggesting FGF-2 is an oncogene. For example, overexpression of FGF-2 isoforms facilitates growth of NIH 3T3 cells in low serum media and also mediates radioresistance of HeLa cells. FGF-2 is also protective against irradiation activation of p53 in the leukemia cells derived from patients with CLL. Although cladribine has been reported to downregulate FGF-2 by inhibiting adenosine deaminase, downregulation of FGF-2 at the transcript and protein levels was also observed in before and after treatment samples from patients treated with 5-azacytidine. We propose an alternative mechanism by which the FGF-2 transcript is degraded after binding to excess miR-195. In patients responsive to treatment with DNA methylation inhibitors, a regional decrease in the methylation status of the CpG island 5′ to miR-195 may lead to increased expression.